High-throughput growth of HfO2 films using temperature-gradient laser chemical vapor deposition. Issue 24 (23rd May 2022) - Tu, Rong; Liu, Ziming; Wang, Chongjie; Lu, Pengjian; Guo, Bingjian; Xu, Qingfang; Li, Bao-Wen; Zhang, Song
Abstract : In this study, HfO2 films were grown using a highly efficient HT-LCVD process with a large gradient (100 K mm −1 ) temperature field, achieving four novel microstructures which appeared simultaneously on a high-throughput sample. Abstract : The use of hafnia (HfO2 ) has facilitated recent advances in high-density microchips. However, the low deposition rate, poor controllability, and lack of systematic research on the growth mechanism limit the fabrication efficiency and further development of HfO2 films. In this study, the high-throughput growth of HfO2 films was realized via laser chemical vapor deposition using a laser spot with a large gradient temperature distribution (100 K mm −1 ), in order to improve the experimental efficiency and controllability of the entire process. HfO2 films fabricated by a single growth process could be divided into four regions with different morphologies, and discerned for deposition temperatures increasing from 1300 K to 1600 K. The maximum deposition rate reached 362 μm h −1, which was 10 2 to 10 4 times higher than that obtained using existing deposition methods. The dielectric constants of high-throughput HfO2 films were in the range of 16–22, which satisfied the demand of replacing the traditional SiO2 layer for a new generation of microchips.